2019
DOI: 10.1002/lno.11171
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic detection of zooplankton diel vertical migration behaviors on the northern Gulf of Mexico shelf

Abstract: Zooplankton respond to light levels, oceanographic conditions, and other cues through diel vertical migrations (DVMs), which can occur at dawn and dusk. However, unraveling the influence of these drivers is difficult without high‐resolution time series data encompassing multiple events that can alter zooplankton DVM. We address this knowledge gap with an interseasonal study using high‐resolution measurements of zooplankton DVMs on the freshwater‐influenced northern Gulf of Mexico shelf. Sampling encompassed 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 90 publications
(128 reference statements)
0
10
0
Order By: Relevance
“…Indeed, all stomach of A. affinis collected at night had food content, while those sampled at daytime were mostly empty. Additionally, the major prey taxa recovered in the stomachs of this species were fish larvae (13 mm) and ostracods (3.3-4.5 mm), organisms typically found in higher densities in epipelagic waters (especially at night) (Parra et al, 2019;Stefanoudis et al, 2019). The nightly ascension of these species has also been reported in the western Indian…”
Section: Discussionmentioning
confidence: 66%
“…Indeed, all stomach of A. affinis collected at night had food content, while those sampled at daytime were mostly empty. Additionally, the major prey taxa recovered in the stomachs of this species were fish larvae (13 mm) and ostracods (3.3-4.5 mm), organisms typically found in higher densities in epipelagic waters (especially at night) (Parra et al, 2019;Stefanoudis et al, 2019). The nightly ascension of these species has also been reported in the western Indian…”
Section: Discussionmentioning
confidence: 66%
“…The “preferendum hypothesis” states that animals remain within a preferred light zone (isolume). Many organisms that comprise DSLs follow isolumes ( 48 51 ), but some organisms do not ( 23 , 52 , 53 ). These contradictory findings may be due to different species and behaviors, physical characteristics of the water column, vertical predator and prey distributions, and uncertainty around light intensity measurements in the twilight zone.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively little attention has been paid to the daytime phototactic behavior of migratory organisms at depth. Kaartvedt et al ( 19 ) showed that mesopelagic fish swam upward beneath a passing storm, Frank and Widder ( 20 ) found that a transient influx of turbid water enhanced light attenuation and induced an upward migration of crustaceans and salps, and other studies show that cloudiness can influence vertical migration behavior on diel timescales ( 21 23 ). McLaren ( 24 ) proposed that during the day, zooplankton may be “resting” in deeper, cooler waters to save energy, and studies estimating migrator excretion and respiration rates at depth assume a constant rate of metabolic activity throughout daylight hours based largely on temperature and animal size ( 15 , 18 ).…”
mentioning
confidence: 99%
“…These results support the notion that surface convergences can select for buoyant particles or organisms capable of swimming against the convergent flows (Genin et al 2005;Höfer et al 2015;D'Asaro et al 2018), but there are more complex interactions below the surface. The disadvantage of the in situ image data is that they only provide a snapshot in time and space, and we have little understanding of how these distributions would change as the surface convergence propagates northward towards the shore and interacts with diel vertical migrations or predator-prey encounters (Greer et al 2018b;Parra et al 2019). Our incorporation of high-resolution modeling served as an attempt to expand the snapshot data towards larger spatiotemporal scales, elucidating biological and physical interactions within these (likely common) features in the nGOM.…”
Section: Discussionmentioning
confidence: 99%